2016
DOI: 10.21548/32-2-1388
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterisation of Oenococcus oeni and Lactobacillus plantarum South African Wine Isolates for Use as Malolactic Fermentation Starter Cultures

Abstract: This study focused on characterising 23 Oenococcus oeni and 19 Lactobacillus plantarum strains isolated from the South African wine environment for the development of potential commercial malolactic fermentation (MLF) starter cultures. These strains were characterised with regards to oenological important characteristics, including the genetic screening for enzyme-encoding genes (enzymes that are involved/implicated in wine aroma modification, as well as enzymes pertaining to the wholesomeness of the final win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 60 publications
2
66
3
1
Order By: Relevance
“…Esterase that originates from wine LAB are responsible for biosynthesis and hydrolysis of esters (Pérez-Martín et al 2013;Sumby et al 2013a, b). Different from previous studies, only three strains were positive for esterase-encoding genes (Lerm et al 2011). The results of the enzymatic screening confirm the presence or absence of the genes, and indicate that these strains have the potential to express the corresponding enzyme; however, they give no indication about the enzymatic activity during MLF in wine.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Esterase that originates from wine LAB are responsible for biosynthesis and hydrolysis of esters (Pérez-Martín et al 2013;Sumby et al 2013a, b). Different from previous studies, only three strains were positive for esterase-encoding genes (Lerm et al 2011). The results of the enzymatic screening confirm the presence or absence of the genes, and indicate that these strains have the potential to express the corresponding enzyme; however, they give no indication about the enzymatic activity during MLF in wine.…”
Section: Discussioncontrasting
confidence: 81%
“…All isolates could survive and degrade L-malic acid under mild conditions (pH 3.8 and 10 % ethanol), but only nine strains could tolerate the harsh condition (pH 3.2 and 14 % ethanol). In this study, O. oeni strains showed a better L-malic degradation capability in the synthetic wine medium than previous studies (Capozzi et al 2010;Ruiz et al 2010;Lerm et al 2011). This result was expected since the synthetic wine media used in this study were designed to meet the essential nutrient demands of different O. oeni strains.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…They also exhibit a wider range and greater spectrum of enzymatic activities than O. oeni, and can contribute to a greater modification of wine aroma. Several authors have demonstrated that many wine-associated lactobacilli contain genes encoding important enzymes that are active under winemaking conditions (Du Toit et al, 2011;Lerm et al, 2011). Besides, the use of L. plantarum has been suggested as a biological acidification method because of its ability to produce high concentrations of lactic acid (Onetto & Bordeu, 2015;Lucio et al, 2016).…”
Section: Malolactic Starter Culturesmentioning
confidence: 99%